Has the Arab Spring Spread to the Caucasus and Central Asia? Explaining Regional Diffusion and Authoritarian Resistance. Issue 3 (4th May 2021) - Aras, Bulent; Oztig, Lacin Idil
ABSTRACT: This article asks the question whether the Arab Spring protests have had a transformative impact on the political regimes of the countries in the Caucasus and Central Asia (CCA). Unlike in the Middle East and North Africa, the protests that took place in the CCA region after 2011 did not result in regime changes. By analysing the political developments in the CCA region between the period of 2011 and 2014, this article argues that rather than encouraging democratic changes, the Arab Spring protests stimulated the learning process of authoritarian rulers in the CCA region by showing the impact of the social media for political mobilization and consequently regime survival. As such, they incentivized the regimes to increase repression, targeting not only the protestors, but also media and the Internet freedom.